Obesidade, leptina e sistema renina-angiotensina: Importância no controle da pressão arterial e regulação autonômica em Camundongos ob/ob e db/db - Hilzendeger, Aline Mourão [UNIFESP] (2009)
The leptin deficient ob/ob mice are insulin resistant and obese. However, the control of blood pressure in this model is not well defined. The goal of this study was to evaluate the role of leptin and the renin-angiotensin system (RAS) in the cardiovascular abnormalities observed in obesity using a model lacking leptin. Leptin is a hormone related to metabolism. It also influences blood pressure, but the mechanisms triggered in this process are not yet elucidated. Angiotensin-I converting enzyme (ACE) regulates cardiovascular functions and recently has been associated with metabolism control and obesity. Here we tried to answer the question whether ACE and leptin could influence blood pressure control being a link between renin-angiotensin system and obesity in ob/ob mice, a model lacking leptin. These mice are obese and diabetic, but have normal 24h mean arterial pressure. Our results show that plasma and lung ACE activities as well as ACE mRNA expression were significantly decreased in ob/ob mice. In agreement with these findings, the hypotensive effect produced by enalapril administration was attenuated in the obese mice. Plasma renin, angiotensinogen, angiotensin I, bradykinin and angiotensin 1-7 were increased, whereas plasma angiotensin II concentration was unchanged in obese mice. Leptin chronic infusion increased renin activity and angiotensin II concentration in both groups and increased ACE activity in ob/ob mice. Acute leptin infusion could restore ACE activity in leptin deficient mice. Moreover, the effect of ACE inhibitor on blood pressure during leptin treatment was not changed in lean, but increased four times in obese mice. In a second part of the study we measured blood pressure in ob/ob and control animals by radiotelemetry combined with fast Fourier transformation before and after both leptin and enalapril treatment. Autonomic function was assessed pharmacologically. Blood pressure during daytime was slightly higher in the ob/ob compared to control mice while no difference in heart rate was observed. Blood pressure response to trimetaphane and heart rate response to metoprolol were greater in ob/ob mice than in control littermates indicating an activated sympathetic nervous system. Heart rate response to atropine was attenuated. Baroreflex sensitivity and heart rate variability were blunted in ob/ob mice, while low frequency of systolic blood pressure variability was found increased. Chronic leptin replacement reduced blood pressure and reversed the impaired autonomic function observed in ob/ob mice. Inhibition of ACE by enalapril treatment had similar effects prior loss of weight. These findings suggest that the RAS is involved in the autonomic dysfunction caused by the lack of leptin in ob/ob mice. In summary, our findings show that the RAS is altered in ob/ob mice, with markedly reduced ACE activity, which suggests a possible correlation between RAS and leptin. These results point to an important interplay between the angiotensinergic and the leptinergic systems and may contribute to clarify the role played by these systems in the pathogenesis of obesity, hypertension, and metabolic syndrome.